Pengaruh Partisipasi Anggaran dan Budget Emphasis terhadap Budgetary Slack pada Rumah Sakit - Junjunan, Nhazib Alqais; Yulianto, Agung (Jurnal Kajian Akuntansi, 2019)
Budgetary slack is a shortage of revenues and over costs that are deliberately incorporated into the budget so that mid-and lower-level managers are more easily reaching the budget objectives. This article aims to analyze the impact of budget participation and budget emphasis partial to slack budgetary in the General Hospital of Cirebon. This study was conducted at 5 public hospitals in Cirebon and by using judgment sampling method obtained 60 respondents as samples. The data analysis techniques in this study use multiple linear regression. Before using regression analysis, the test was carried out in advance, which included the validity test and the classical assumption test, which included the test of normality, multicollinearity test, and heteroskedasticity test. Results of the study showed that a partial participation in budget and budget emphasis affected the slack budgetary.Keywords: Budgetary participation; budget emphasis; and budgetary slack.